Validating Psychosocial Measures Of Social Support, Coping Strategies, And Burnout In Special Educational Teachers In Jambi - Iza Nurjanah; Marlina Marlina (Universitas PGRI Yogyakarta, 2026)
Teachers in Special Education face various complex professional and emotional challenges. In practice, they are required to possess strong psychological resilience, adaptive social skills, and the ability to manage stress effectively. This study aims to examine the validity and reliability of three psychosocial instruments used to measure social support, coping strategies, and burnout among Special Education teachers in Jambi Province. The instruments consist of a social support scale (12 items), a coping strategy scale (28 items), and a burnout scale (42 items). This study employed a descriptive quantitative approach involving 30 purposively selected Special Education teacher respondents. Validity testing was conducted using Pearson Product-Moment correlation, while reliability testing employed Cronbach’s Alpha. The results showed that all items in the social support instrument were valid and reliable (α = 0.852). In the coping strategy instrument, two items were invalid and removed, resulting in high reliability (α = 0.940). In the burnout instrument, 10 items were invalid and eliminated, yielding very high reliability (α = 0.960). These findings indicate that the three instruments are suitable for measuring the psychosocial aspects of Special Education teachers in Indonesia. Keywords: validity, reliability, special education teachers, social support, coping strategies, burnout